Antipanic-like effect of esketamine and buprenorphine in rats exposed to acute hypoxia - Maraschin, Jhonatan Christian; Frias, Alana Tercino; Hernandes, Paloma Molina; Batistela, Matheus Fitipaldi; Martinez, Lucas Motta; Joca, Sâmia Regiane Lourenço; Graeff, Frederico Guilherme; Audi, Elisabeth Aparecida; Spera de Andrade, Telma Gonçalves Carneiro [UNESP]; Zangrossi, Hélio (Elsevier, 2022)
The antidepressant effect of ketamine has been widely acknowledged and the use of one of its enantiomers, S-ketamine (esketamine), has recently been approved for the clinical management of treatment-resistant depression. As with ketamine, the non-selective opioid receptor-interacting drug buprenorphine is reported to have antidepressant and anxiolytic properties in humans and rodents. Given the fact that antidepressant drugs are also first line treatment for panic disorder, it is surprising that the potential panicolytic effect of these compounds has been scarcely (ketamine), or not yet (buprenorphine) investigated. We here evaluated the effects of ketamine (the racemic mixture), esketamine, and buprenorphine in male Wistar rats submitted to a panicogenic challenge: acute exposure to hypoxia (7% O2). We observed that esketamine (20 mg/kg), but not ketamine, decreased the number of escape attempts made during hypoxia, and this effect could be observed even 7 days after the drug administration. A panicolytic-like effect was also observed with MK801, which like esketamine, antagonizes NMDA glutamate receptors. Buprenorphine (0.3 mg/kg) also impaired hypoxia-induced escape, an effect blocked by the non-selective opioid receptor antagonist naloxone, indicating an interaction with classical ligand sites, such as µ and kappa receptors, but not with nociception/orphanin FQ receptors. Altogether, the results suggest that esketamine and buprenorphine cause rapid-onset panicolytic-like effects, and may be alternatives for treating panic disorder, particularly in patients who are refractory to standard pharmacological treatment.
Keywords: Buprenorphine; Esketamine; Hypoxia; Ketamine; Panic disorder